Fermi- to non-Fermi-liquid crossover and Kondo behavior in two-dimensional (Cu2/3V1/3)V2S4. (23rd May 2019) - Gauzzi, A; Moutaabbid, H; Klein, Y; Loupias, G; Hardy, V
Abstract: By means of a specific heat ( C ) and electrical resistivity ( ) study, we give evidence of a pronounced Fermi liquid (FL) behavior with sizable mass renormalization, , up to unusually high temperatures ̃70 K in the layered system (Cu2/3 V1/3 )V2 S4 . At low temperature, a marked upturn of both C and is suppressed by magnetic field, which suggests a picture of Kondo coupling between conduction electrons in the VS2 layers and impurity spins of the V 3+ ions located between layers. This picture opens the possibility of controlling electronic correlations and the FL to non-FL crossover in simple layered materials. For instance, we envisage that the coupling between layers provided by the impurity spins may realize a two-channel Kondo state.